Structure and dimerization of the teleost transmembrane immunoglobulin region - MERLINO, ANTONELLO; MAZZARELLA, LELIO; S. Varriale; M. R. Coscia; U. Oreste (Journal of Molecular Graphics and Modelling, 2008)
The immune system cells express activating receptors, which consist of a dimeric ligand-binding molecule associated with a signal transducing dimer. The communication between the receptor partners depends primarily on the interactions between their membrane-embedded segments. In the B cell receptor (BCR) the sequence traversing the lipid bilayer of the immunoglobulin (IgTM) is highly conserved among species. We have investigated the association of the IgTM regions of the BCR of the Antarctic teleost Chionodraco hamatus. The nucleotide sequence of the entire immunoglobulin chain has been determined and the length, polarity, and structure of the IgTM region have been thoroughly analyzed. Structural models of the IgTM homodimer were also obtained by performing several MD simulations in a lipid bilayer using, as a starting model, two copies of the IgTM helix placed at various relative orientations and distances. Despite a certain degree of conformational heterogeneity, the predicted models of the IgTM homodimer display similar packing interfaces, characterized by a high degree of surface complementarity. The residues presumably responsible for the interaction and, consequently for the receptor stability have been identified in this manner.